Multiple Functions of KBP in Neural Development Underlie Brain Anomalies in Goldberg-Shprintzen Syndrome - Chang, Hsin-Yun (Front Mol Neurosci, 2019)
Kinesin-binding protein (KBP; KIF1BP; KIAA1279) functions as a regulator for a subset of kinesins, many of which play important roles in neural development. Previous studies have shown that KBP is expressed in nearly all tissue with cytoplasmic localization. Autosomal recessive mutations in KIAA1279 cause a rare neurological disorder, Goldberg-Shprintzen syndrome (GOSHS), characterized by microcephaly, polymicrogyria, intellectual disability, axonal neuropathy, thin corpus callosum and peripheral neuropathy. Most KIAA1279 mutations found in GOSHS patients are homozygous nonsense mutations that result in KBP loss-of-function. However, it is not fully understood how KBP dysfunction causes these defects. Here, we used in utero electroporation (IUE) to express KBP short hairpin RNA (shRNA) with green fluorescent protein (GFP) in neural progenitor cells of embryonic day (E) 14 mice, and collected brain slices at different developmental stages. By immunostaining of neuronal lineage markers, we found that KBP knockdown does not affect the neural differentiation process. However, at 4 days post IUE, many cells were located in the intermediate zone (IZ). Moreover, at postnatal day (P) 6, about one third of the cells, which have become mature neurons, remained ectopically in the white matter (WM), while cells that have reached Layer II/III of the cortex showed impaired dendritic outgrowth and axonal projection. We also found that KBP knockdown induces apoptosis during the postnatal period. Our findings indicate that loss of KBP function leads to defects in neuronal migration, morphogenesis, maturation, and survival, which may be responsible for brain phenotypes observed in GOSHS.